Production of chemokines by mesenchymal stromal cells established from inflamed human gingiva and its modulation by lipopolysaccharide - Marina Radanović; Miodrag Čolić (Биомедицинска истраживања, 2025)
Introduction: The role of gingiva-derived stromal cells (GMSCs) in chronic periodontitis is poorly understood. Since GMSCs modulate the inflammatory and immune responses this study aimed to investigate the production of chemokines by GMSCs established from chronic periodontitis tissue under basal conditions and after stimulation with lipopolysaccharide (LPS), which is a main trigger of gingivitis/periodontitis. Methods: GMSCs, established from periodontitis-affected gingival tissue, were characterized by flow cytometry and their differentiation capability. GMSCs, from the 5th passage, were cultivated either alone or with LPS for 24 hours followed by the determination of chemokine levels in culture supernatants by a sandwich ELISA assay. Results: More than 95% of GMSCs expressed all three (CD90, CD73, and CD105) MSC markers, with a relatively high potential to differentiate into osteoblasts and chondroblasts and a low adipogenic differentiation capability. Of all chemokines, the basal production of interleukin-8 (IL-8) (186.2 ± 23.4 pg/mL) and Monocyte Chemoattractant Protein-1 (MCP-1) (103.5 ± 12.7 pg/mL) was highest, followed by the levels of Growth-Related Oncogene (GRO)-? (16.2 ± 2.4 pg/mL) and Regulated Upon Activation, Normal T-cell Expressed and Secreted (RANTES) (10.3 ± 1.4 pg/mL ). The basal production of Interferon (IFN)-?-Induced Protein 10 kDa (IP-10) was undetectable. When stimulated with LPS, GMSCs significantly up-regulated the production of all chemokines. Their levels (pg/mL) were as follows: IL-8 - 926.4 ± 84.0; MCP-1 - 424.0 ± 33.2; GRO-? - 109.3 ± 12.2; RANTES - 154.9 ± 6.6; IP-10 - 211.6 ± 15.7. Conclusion: GMSCs may promote or suppress periodontal inflammation depending on produced chemokines and their balance.
Keywords: gingiva; mesenchymal stromal cells; periodontitis; chemokines